Estrategias de afrontamiento y autoestima en personas atendidas en la sala de primera acogida del hospital provincial general docente – Riobamba, periodo 2017 - 2018. - Daniela Noemi, Barriga Valdiviezo (2020)
This research project analyzes coping and self-esteem strategies in people served in the first reception room of the ¨Hospital Provincial General Docente de Riobamba¨. It was done with a sample of 45 medical records of women victims of gender violence in a corresponding range of 18 to 50 years. Once these data were obtained, it was shown that the most vulnerable population at risk are between the ages of 43-50 years with 31.11%. The most commonly used coping strategy for women victims of violence are coping strategies of the Emotional Avoidance type that equals 10 women with 21.73% and the type of self-esteem they possess is High Positive Self-Esteem with 29 patients equivalent to 63.04%. The data reflected result in women victims of gender-based violence having as a coping strategy emotional avoidance, but strategies focused on problem solving should be incited, instilled and generated so that they can cope with the stress situation in the best way, and in an assertive way the problems that you will face throughout everyday life, this will therefore help to improve and maintain a healthy self-esteem.